Microwave-induced conductance replicas in hybrid Josephson junctions without Floquet—Andreev states - Haxell, Daniel Z.; Coraiola, Marco; Sabonis, Deividas; Hinderling, Manuel; ten Kate, Sofieke C.; Cheah, Erik; Krizek, Filip; Schott, Rüdiger; Wegscheider, Werner; Belzig, Wolfgang; Cuevas, Juan Carlos; Nichele, Fabrizio (Nature communications, 2023)
Light–matter coupling allows control and engineering of complex quantum states. Here we investigate a hybrid superconducting–semiconducting Josephson junction subject to microwave irradiation by means of tunnelling spectroscopy of the Andreev bound state spectrum and measurements of the current–phase relation. For increasing microwave power, discrete levels in the tunnelling conductance develop into a series of equally spaced replicas, while the current–phase relation changes amplitude and skewness, and develops dips. Quantitative analysis of our results indicates that conductance replicas originate from photon assisted tunnelling of quasiparticles into Andreev bound states through the tunnelling barrier. Despite strong qualitative similarities with proposed signatures of Floquet–Andreev states, our study rules out this scenario. The distortion of the current–phase relation is explained by the interaction of Andreev bound states with microwave photons, including a non-equilibrium Andreev bound state occupation. The techniques outlined here establish a baseline to study light–matter coupling in hybrid nanostructures and distinguish photon assisted tunnelling from Floquet–Andreev states in mesoscopic devices. The authors study conductance replicas emerging under microwave irradiation in the tunnelling spectrum of Josephson junctions in InAs/Al heterostructures, focusing on distinguishing the signatures of Floquet-Andreev states (FASs) from those of photon-assisted tunneling (PAT). They establish that PAT largely dominates the response to microwave radiation in their device.